Prevalence of Diabetes Mellitus in Hepatitis C Patients in Wazirabad Tehsil of Gujranwala District of Pakistan: hepatitis C in Diabetic patients (Baghdad Science Journal, 2020)
Hepatitis, a condition of liver’s inflammation that can be self-limiting or, in certain chances, it may lead to liver cancer, fibrosis or cirrhosis. Hepatitis viruses mainly cause hepatitis in the world. People with hepatitis C have predominant chances to develop diabetes as HCV virus participates in causing type 2 diabetes. HCV virus causes pathogenesis in two ways: it either directly destroys the β cells of pancreas or contributes to the specific autoimmunity of β cells. The present cross sectional study was done in Wazirabad Tahsil of Gujranwala District to analyze the percentage of patients suffering from hepatitis C who had the risk of diabetes mellitus. For this research work, demographic information and data about any other medical history were collected by using a questionnaire. Blood samples were collected from hospital and real time PCR was performed to measure the viral load and blood sugar was measured by using glucometer. Data were then analyzed by using statistically designed software. A total of 29.33% patients, having hepatitis C, were found to be diabetic in Tehsil Wazirabad. 14.70% male and 38.59% female patients having hepatitis C were diabetic. From results shown that the patients of hepatitis C are at higher risk to develop diabetes, therefore; it is supposed that persons having hepatitis C should regularly visit doctors for routine check-up of diabetes and change their life style to reduce the risk of developing diabetes.